Effects of Momordica Charantia (Karela/bitterguord) in Type 2 Diabetic Patients Taking Allopathic Drugs: A pilot study - Rauniyar, G. P.; Sinha, R.; Chapagain, K.; Maskey, R.; Pandey, D. R. (Kathmandu University Medical Journal, 2021)
Background Momordica charantia is evolving as supplementary therapy in type 2 diabetes mellitus. Animal studies reveal its anti-diabetic and lipid lowering property. However, clinical studies with human subjects are very few. Objective To find out the effects of Momordica charantia supplements on glycemic and lipid profile among type 2 diabetes mellitus patients taking allopathic drugs. Method A comparative study was conducted in internal medicine department of B P Koirala Institute of Health Sciences, Dharan from July 2015 to May 2016 after ethical clearance. Twenty two uncomplicated type-2 diabetes mellitus patients were enrolled. Group A patients were supplemented with allopathic drug (oral anti-diabetic agents) only and Group B with add on treatment of 200 ml juice of Momordica charantia along with allopathic drug daily for ninety days. Fasting, post prandial blood sugar and lipid profile levels were compared between baseline and ninety days post supplementation. Data was collected and entry was done in Statistical Packages for Social Services version 20.0, using independent t test with p < 0.05. Result Add on treatment with 200 ml of Momordica charantia along with anti-diabetic drug daily significantly reduced fasting (p= < 0.0001) and post prandial blood sugar (p=< 0.0001). Treatment with anti-diabetic drugs only reduced fasting (p = 0.0008) and post-prandial blood sugar but the reduction was not significant ((p =0.0001). There was improvement in lipid profile by both anti-diabetic drugs alone and Momordica charantia along with anti-diabetic drug, but it was not significant. Conclusion Add on treatment with 200 ml/day juice of Momordica charantia is effective in glycaemic control in type-2 diabetes mellitus patients as compared to the allopathic treatment alone.